Ontogeny of the testicular excurrent duct system of male Japanese quail (Coturnix japonica): A histological, ultrastructural, and histometric study. Issue 3 (13th November 2021) - Ibrahim, Mohammed I. A.; Zakariah, Musa; Molele, Reneilwe A.; Mahdy, Mohamed A. A.; Williams, June H.; Botha, Christo J.
Abstract: The testicular excurrent duct system undergoes several physiological and morphological changes during the reproductive stage or breeding season in mammals, birds, and reptiles. Studies on normal age‐related histomorphological changes in the excurrent duct system of Japanese quails ( Coturnix japonica ) remain unreported, despite the extensive use of this bird as an avian model in research studies. The current study investigated the histological, ultrastructural, and histometric changes in the testicular excurrent duct system of the Japanese quail during three reproductive stages, namely prepubertal, pubertal, and adult. Simple squamous to low cuboidal cells formed the epithelia of the rete testis in prepubertal and pubertal birds, while in adult birds the lining was low cuboidal to cuboidal. In pubertal and adult birds, the nonciliated Type I epithelial cells of the proximal efferent duct displayed a subapical endocytotic apparatus comprising coated pits, coated apical tubules, and endosomes. There was a significant increase ( p  ≤ .001) in epithelial heights of all ducts of the excurrent duct system in the mature, sexually active, adult birds when compared to the other age groups. The luminal and tubular diameters, and the cross‐sectional areas of efferent ducts and the epididymal duct unit increased significantly ( p  ≤ .001) with age. It is concluded that the morphology and morphometry of the excurrent ducts of the testis of the Japanese quail change as birds mature. Abstract : Baseline histological and ultrastructural variations, as well as histometric measurements in the testicular excurrent duct system of prepubertal, pubertal, and sexually active, adult Japanese quails, are reported. There were age‐ and reproductive stage‐related histological, ultrastructural, and histometric changes in all ducts of the testicular excurrent duct system of the Japanese quail as they matured.